Zycie Aleksandra Fleminga. - Maurois, Andre, 1885-1967. ([Warszawa] Czytelnik, 1962)
Biography of the British bacteriologist Alexander Fleming.
Keywords: Fleming, Alexander, -- 1881-1955.; Bacteriologists -- Great Britain -- Biography; Penicillin -- History